2019
DOI: 10.1002/smi.2912
|View full text |Cite|
|
Sign up to set email alerts
|

The relationship between bicultural identity, acculturative stress, and psychological well‐being in multicultural adolescents: Verification using multivariate latent growth modelling

Abstract: This study aimed to examine causal relationships between bicultural identity, acculturative stress, and subjective well-being among multicultural adolescents. Secondary longitudinal data that were obtained from 1,635 multicultural adolescents were analysed. The results showed that bicultural identity had a positive effect on psychological well-being and a negative impact on acculturative stress; in addition, greater acculturative stress was associated with lower psychological well-being. Finally, bicultural id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…These results indicated that there was significant variance in both intercepts and both slopes across individuals permitting further examination. Following common LGM practices (e.g., Bae, 2020), we regressed the intercept of the outcome onto the intercepts of the two predictors, and the slope of the outcome onto the slopes of the two predictors. This allows us to test for the hypothesised slope effects together with intercept effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that there was significant variance in both intercepts and both slopes across individuals permitting further examination. Following common LGM practices (e.g., Bae, 2020), we regressed the intercept of the outcome onto the intercepts of the two predictors, and the slope of the outcome onto the slopes of the two predictors. This allows us to test for the hypothesised slope effects together with intercept effects.…”
Section: Resultsmentioning
confidence: 99%
“…Following common LGM practices (e.g., Bae, 2020), we regressed the Note: Each model reflects job insecurity and employability for a given year predicting the next year's mental health. For example, results in the first row describe job insecurity and employability in 2001 predicting mental health in 2002.…”
Section: Tests Of the Functional Similarity Hypothesismentioning
confidence: 99%
“…The second hypothesis assumed that ethnic identity would affect mental health problems negatively. It is known that a higher level of ethnic identity is related to mental health and the acculturation process (22,(66)(67)(68). Ethnic identity development is defined as a process related to feelings, opinions, thoughts, and actions related to ethnic group affiliation (62,86).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research suggests that bicultural identity is associated with the lower levels of depression and anxiety (Tikhonov et al, 2019), which are known risk factors for cigarette smoking (Fluharty et al, 2017). Recent research also shows that bicultural identity is positively associated with positive well-being (e.g., Bae, 2020), a known protective factor against cigarette smoking (Lappan et al, 2020).…”
Section: The Associations Between Biculturalism and Cigarette And Bet...mentioning
confidence: 99%